LYGAEIDAE SCHILLING, 1829 OILASINING FAUNISTIK TAHLILI - Romanov , D.R.; Аbdullaev , I.I (Actual problems and prospects of the study of the fauna, 2024)
This article provides information on the species composition, distribution, biotope and trophic groups of representatives belonging to the Lygaeidae family. Studying these species in the territory of Uzbekistan, determining the species composition will serve as an important base for the fauna of Uzbekistan in the future.